2011
DOI: 10.1063/1.3650455
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor behavior in multiferroic BiMn2O5 ceramics

Abstract: In polycrystalline BiMn 2 O 5 , a broad thermal stimulated depolarization current curve has been observed in the range from 10 K to 300 K and the pyroelectric coefficient determined. In magnetic susceptibility measurements reported in the literature, features appearing in the pyroelectric coefficient could also be identified for the same temperatures, suggesting a connection between electric and magnetic data above the Néel temperature. A detailed study of the dielectric constant from 240 K to 700 K for an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…We note that VF was fitted from 330 to 390 K. The crossover from Arrhenius to VF dependence is consistent with DSC measurements, which exhibited a change in the slope of the temperature dependence of the heat flow in the vicinity of 325 K. Hence, we deduce that the BM ceramics exhibits the glassy features corresponding to structural disorder. It is worth mentioning that the occurrence of disorder behavior also related to VF dependence, fulfilled in the 520−570 K range, was previously reported for multiferroic BiMn 2 O 5 ceramics …”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…We note that VF was fitted from 330 to 390 K. The crossover from Arrhenius to VF dependence is consistent with DSC measurements, which exhibited a change in the slope of the temperature dependence of the heat flow in the vicinity of 325 K. Hence, we deduce that the BM ceramics exhibits the glassy features corresponding to structural disorder. It is worth mentioning that the occurrence of disorder behavior also related to VF dependence, fulfilled in the 520−570 K range, was previously reported for multiferroic BiMn 2 O 5 ceramics …”
Section: Resultssupporting
confidence: 60%
“…It is worth mentioning that the occurrence of disorder behavior also related to VF dependence, fulfilled in the 520−570 K range, was previously reported for multiferroic BiMn 2 O 5 ceramics. 24 The hydrostatic pressure test conducted in isobaric conditions, P = 800 and 1600 MPa, was conducted in the 253-363 K range. The relaxation process visible in isobaric ε"(f)…”
Section: Resultsmentioning
confidence: 99%
“…In the previous investigation [32] we discovered a pyroelectric effect in the range of 77e500 K in the a-axis direction of BiMn 2 O 5 monocrystals. The pyroelectric properties were also reported [33,34] for polycrystalline BiMn 2 O 5 in a wide temperature range. The pyroelectric current changed its sign with switching the direction of the poling field of the polycrystalline material [34].…”
Section: Introductionmentioning
confidence: 77%
“…The studies of frequency dependence of the dielectric constant revealed [35] a low temperature dielectric relaxation, attributed to the hopping of charge between Mn 3þ and Mn 4þ , and high temperature dielectric relaxation, related to oxygen defects. The analysis of the dielectric constant at different conditions [33] suggested a relaxor type ferroelectric behavior at high temperatures. However, no direct evidence of ferroelectric hysteresis behavior was observed at room temperature [30].…”
Section: Introductionmentioning
confidence: 98%
“…However, it is of very difficulty in garnering single crystalline phase YbMn 2 O 5 with controlled microstructure owing to process characters [12]. In fact, several wet chemical methods, including sol-gel method [13] and hydrothermal synthesis [14,15], were developed to synthesize RMn 2 O 5 powders. Among them, hydrothermal synthesis has been receiving much interest due to its great advantages, such as low process temperature, one-step synthesis procedure, and easy handing [16,17], for example, YbMn 2 O 5 nanorods with diameter ~ 40 nm and ~ 500 nm in length were synthesized by a simple hydrothermal method [18].…”
Section: Accepted Manuscriptmentioning
confidence: 99%